Dissecting the histological features of lupus nephritis highlights new common patterns of injury in class III/IV. Issue 12 (8th August 2022) - Bolognesi, Maddalena Maria; Capitoli, Giulia; Galimberti, Stefania; Cattoretti, Giorgio; Bajema, Ingeborg; Bruijn, Jan A; Cook, H Terence; Noel, Laure-Helene; Pagni, Fabio; Ferrario, Franco; Wester Trejo, Maria; L'Imperio, Vincenzo
Abstract : Objective: The International Society of Nephrology/Renal Pathology Society classification is the gold standard for the characterisation of lupus nephritis (LN) on renal biopsy, with therapeutic repercussions. Its recent revision simplified the current class subdivisions, eliminating the S/G forms of class IV, although data on a possible pathogenetic/clinical value of this subdivision are still contradictory. Methods: 353 renal biopsies from Belimumab International Study in LN were assessed through central pathology review. Univariate logistic models and a decision tree were performed on 314 adequate biopsies to evaluate the impact of histological features on focal/diffuse classes. Removing class I/II (n=6) and 'pure' class V (n=34), principal component analysis (PCA) and heatmap were used to explore similarities among III, IVS and IVG biopsies either incorporating or not the mixed classes (+V, n=274). Finally, a method aimed at partitioning the cases into k clusters based on their similarity (KMeans), was used to study features from the cohort of 'pure' class III/IVS/IVG cases (n=214) to determine alternative subdivisions based on phenotypic data. Results: Segmental endocapillary hypercellularity (EH) was prevalent in class III, global EH, wire loops, hyaline thrombi and double contours were hallmarks of class IVG, with IVS cases showing intermediate characteristics. Heatmap and PCA confirmed the segregation of these features among classes, showing better segregation for focal/diffuse LN as compared with the mixed classes (+V). KMeans revealed the presence of two main clusters, membranoproliferative-like (n=83) or vasculitis-like (n=131). Conclusions: This study reveals new phenotypic forms of LN surpassing the traditional classes as determined by the current classification. Future validation and confirmation are required to confirm these findings.